Republic of Latvia : Staff Report for the 2005 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
The staff report for the 2005 Article IV Consultation on the Republic of Latvia highlights the economic outlook and mid-term risks. A sound policy framework and far-reaching structural reforms supported this performance, including a prudent fiscal policy that underpinned the exchange rate peg. The ongoing credit boom and faster real wage growth are expected to support private domestic demand while a sharp increase in net European Union (EU) grants would also boost public spending. Efficiently allocating EU funds for infrastructure was seen as a key element of a framework for promoting efficient resource allocation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet